The swap - Shade, John; Leondopoulos, Jordan, 1938-; De Niro, Robert; Cannon Productions; Cinetel Films ([Los Angeles, CA] : Cannon Productions, 1979)
Small-time hood Vito is released from jail after serving a twelve-year sentence. His only desire is to find the killer of his younger brother Sammy, a film editor murdered ten years earlier. His search leads him to the people Sammy spent his last weekend with, a group of wealthy people that involved his brother in their decadent lifestyle. Vito soon discovers that Sammy was involved in more than film editing.
Originally released as a motion picture in 1969 under the title Sam's song. Re-cut in 1979 as "The swap."
Robert De Niro, Jennifer Warren, Jerry Micky, Terrayne Crawford, Martin Kelley, Anthony Charnota, Lisa Blount, Sybil Danning.
Cinematographer, Alex Phillips, Jr.; editor, Arline Garson; music, Gershon Kingsley.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November 20, 2015).
Keywords: Revenge -- Drama; Motion picture producers and directors -- Drama; Detective and mystery films; Feature films; Internet videos; Streaming video